Study of the effect of fiber orientation on the flexural strength of epoxy-coated glass fiber-reinforced composite materials - M. Ali , Hisham; R. Mohammed, Abdurahman (University of Thi-Qar Journal of Science, 2019)
In this paper, a composite material was prepared with layers of glass fiber. Six layers were arranged with unidirectional angles In addition angles with tilted layers, any symmetrical angle-ply laminate three layers are . In Hand Lay-up¸the composite material consists of epoxy resin as a base material and layers of fiberglass as a reinforced material with weight fracture of 25% and 12%.respectivty The research was carried out in two stages: First, the synthesis of the composite material of the samples were then processed at different temperatures . In the second stage, the three-point bending test was performed on the samples. The results have shown that the composite material is varying with directions. In the orientation of the fibers, the strength reaches at maximum values i.e. the angles While in the direction of the angles The strength at the minimum values and the values of strength between these two extremes, i.e. angles ( ) As for the symmetrical ply Laminated, the strength increases with the presence of the(0°) layer.